Pengaruh Hidden Curriculum terhadap Pembinaan Karakter Religius Peserta Didik di Dayah Jeumala Amal Pidie Jaya dan Dayah Al-Furqan Pidie - Hayati, Amal; M. Nur, Azhar; Dahliana, Syarifah (Tadabbur: Jurnal Peradaban Islam, 2021)
Hidden curriculum helps manifest the development of students’ religious characters; however, it is often neglected and not used properly in the learning process. The questions posed in this study include: How is the implementation of the hidden curriculum in the development of the religious characters of students? To what extent the hidden curriculum influences the development of the religious characters of students? and What is the impact of the hidden curriculum on the formation of the religious characters of students? This mixed methods study obtained data by means of questionnaire, interview, and observation. The subject of the study had a sample size of 153. The study employed the SPSS ver. 25 to analyze the quantitative data, whereas the qualitative data were presented descriptively. The findings indicate that the hidden curriculum has been applied inside and outside the classroom. The study revealed that the hidden curriculum implemented at Dayah Jeumala Amal and Dayah Al-Furqan reached the medium level of 40% and of 34.78%, respectively and also created students with high religious characters of 51.54% and of 43.48%, respectively. Further, the simple linear regression test obtained the value of 0.00, at the level of significance α = 0.005, indicating that there was an influence of the hidden curriculum on the development of the religious characters of students. The influences of the hidden curriculum in the forms of role model, habituation, coaching, and attitudes from an educator have resulted in the birth of exemplary values ​​that are more long lasting and impactful within the students. In addition, the influences in the social and environmental forms have triggered the establishment of a harmonious relationship with other people and yielded an attitude of concern for the environment in which the students live. Moreover, the implementation of the hidden curriculum in the form of worship carried out in schools has also enabled the development of religious attitudes, including honesty, patience, and trustworthiness, within the students.